Bridging Traditional Practices and Islamic Finance: Educational Insights - Su'ib, Mohammad Syaiful; Salima, Salima (Journal of Educational Management Research, 2025)
This study examines the implementation of cattle herding as a cooperative model between livestock owners and managers, bridging traditional practices with Islamic finance principles. Using a descriptive qualitative method, data were collected through interviews, observations, and document analysis involving cattle farmers and herding business actors. The findings indicate that while the system operates on mutual trust and shared benefits, several aspects do not fully align with sharia economic principles. These include issues with contract clarity (akad), transparency in profit distribution, and justice among the parties. Some practices reflect the mudharabah and musaqah contract models in Islamic finance but require stronger institutionalization and legal understanding. This study contributes to the development of Islamic economic thought by contextualizing traditional cooperative models within sharia-compliant business ethics. Furthermore, it highlights the importance of integrating local wisdom with Islamic economic principles to promote sustainable, fair, and religiously appropriate practices in rural communities. The implications for educational management emphasize the need to incorporate Islamic finance principles into rural economic education, fostering ethical, fair, and sustainable economic practices aligned with sharia values.